Analysis of the Performance of Selected Large-Cap Mutual Funds of India - Singh, Raavi; Kulkarni, Ketki (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2023)
Mutual funds are considered the most accessible and simplest investment avenue for investors. As the investment focus is not only on one particular sector but on many other sectors as well. The money pooled from the investors is invested in a diversified portfolio thus giving collective returns to the investors. This research study focuses on the performance analysis of the open-ended scheme which focuses primarily on the equity large-cap funds. For the research study, 27 equity large-cap mutual funds were selected from India. The study aims to examine the performance of selected large-cap mutual funds and to identify which schemes to invest in relation to the risk involved and the amount of return obtained from each of them. The data obtained for research was secondary and the analysis was done by using various statistical tools and techniques like beta, Sharpe ratio, Jensen ratio, Treynor ratio, and ordinary least square regression (OLS). The findings of the study highlighted that there is a significant relation between risk and return. Results further depicted that Axis Bluechip Fund - Direct Plan-Growth had a beta value of more than 1.0 indicating that the underlying stock is more volatile and the R-square value explained that all independent variables explain 92.35% of returns (dependent variable).